Impact of introducing a national policy for prenatal Down syndrome screening on the diagnostic invasive procedure rate in England. (9th April 2013) - Morgan, S.; Delbarre, A.; Ward, P.
ABSTRACT Objective To evaluate the impact of the introduction of a Down syndrome screening policy in England, including implementation of the first‐trimester combined screening test, on reducing prenatal invasive diagnostic procedure rates. Methods All English cytogenetic laboratories were asked to submit data from the fiscal years 2003/2004 until 2011/2012 on all samples received from prenatal invasive procedures, including those that were undertaken following a higher‐risk Down syndrome screening result. Results There was a gradual decline in the number of invasive procedures undertaken subsequent to a positive Down syndrome screening result in England, from 36 968 in 2003/2004 to 11 446 in 2008/2009, with only a relatively small subsequent decrease, to 10 215, in 2011/2012. This corresponds to a 72% reduction in the number of referrals received by the cytogenetic laboratories over a 9‐year period and correlates with the national policy of implementing the combined screening test in place of second‐trimester screening, which has reduced the overall screen‐positive rate to 3.1% from an initial level of 6.0%. Conclusions Implementation of a national Down syndrome screening policy based on the combined screening test has significantly reduced the number of invasive tests performed. However, as the combined screening test has become the replacement for second‐trimester testing and has been almost completely implemented it appears that improvements in screening using current approaches may have reached their limits. Copyright © 2013 ISUOG. Published by John Wiley & Sons, Ltd.